Islamic Awareness on Social Media: Faith-Based Responses to Cyberbullying Against Individuals with Disabilities - Billah, Muktashim; Kemala, Rosmalina; Larhzizer, Fouad; Harakan, Ahmad (ADDIN, 2025)
This study examines how Islamic awareness influences social media users’ responses to cyberbullying, with a particular focus on individuals with disabilities. The rising cases of cyberbullying targeting vulnerable groups, especially individuals with disabilities, highlight the need for more effective approaches to addressing this negative behavior. In this context, understanding the role of religious values, particularly Islamic teachings, in shaping online behavior becomes crucial. This research aims to explore how Islamic principles such as justice, empathy, and compassion contribute to respectful and supportive responses in online interactions. Using a qualitative approach, 3,869 comments were collected and analyzed from social media platforms, including Instagram, Facebook, and TikTok. The findings reveal a consistent pattern of supportive and empathetic responses, with users often framing their interactions through Islamic teachings, which deters hostile behavior and encourages positive engagement. Compared to previous studies emphasizing regulatory approaches to prevent cyberbullying, this study suggests that internalized religious values may provide a more foundational framework for fostering ethical online conduct. The findings underscore the potential of Islamic awareness as a values-based approach to cyberbullying prevention, offering a culturally resonant solution to complement existing strategies. This study contributes to the field of digital ethics by highlighting the role of religious values in promoting inclusive digital interactions and opens avenues for further research into integrating religious ethics into digital literacy programs.